Amino-functionalization-assisted construction of CoP/N, P co-doped graphene to enhance stable lithium storage via electrostatic interaction and strong bonds. (20th February 2023) - Lan, Bo; Zhang, Xueqian; Zhao, Lianyu; Wang, Peng; Wei, Chuncheng; Wang, Yishan; Wen, Guangwu
Highlights: CoP/NPC is synthesized by an amino-functionalization-assisted one pot self-assembly method. Electrostatic attraction promotes uniform loading of CoP on N, P co-doped graphene. Establishing Co-O-C and C-P strong bonds between CoP and graphene enhances the structural strength. Pseudocapacitive effect dominates with long cycling stability and rate capability. The method can be applied to prepare many highly stable graphene composite anodes. Abstract: Compounding CoP nanoparticles with graphene can serve as promising anode materials for high-performance lithium-ion batteries. However, the weak binding and dispersion between CoP and graphene usually lead to poor structural stability limiting the lithium storage performance. Herein, an amino-functionalization-assisted one pot self-assembly method is employed to synthesize CoP/nitrogen, phosphorus co-doped graphene composites (CoP/NPG) with a highly stable 3D porous structure. The negatively charged phytic acid can act as a bridging connection between the positively charged amino-functionalized graphene and Co 2+ by strong electrostatic attraction, ensuring the synthesized CoP nanoparticles are uniformly distributed on NPG sheets with high conductivity and plenty of active centers. Meanwhile, establishing strong C–P and Co–O–C surface chemical bonds between CoP and NPG improves the structural strength and promotes fast electron/ion transport, which effectively alleviates the volume expansion of CoP. Benefiting from these advantages, the CoP/NPG electrode displays high lithium storage capacity (917.9 mAh g − 1 at 0.5 A g − 1 after 600 cycles), ultra-long cyclic stability (434.8 and 350.5 mAh g − 1 at 3.0 and 5.0 A g − 1 after 3000 cycles) and fast pseudocapacitive charge storage (contribution even up to 97% at 2.0 mV s − 1 ). This strategy offers promising prospects for the preparation of highly stable anode materials. Graphical abstract: Image, graphical abstract